(untitled) (Research, Society and Development, 2022)
Sorghum is a Poaceae plant with C4 metabolism native to Africa, it has high adaptation to arid and semi-arid regions, showing good resistance to water deficit and to different types of soils. Often used in animal and human food and in the production of biofuel, the main one being animal feed. Forage sorghum is a good alternative for sustainable production systems in family farming, as its adaptive and production characteristics make it possible to replace corn, which has a more demanding and longer cultivation. Organic fertilization in the production of sorghum can strengthen its importance for family farming, as it allows the small producer to use what he already has on his property and achieve an advantageous production. The work aimed to analyze the production of sorghum with different organic fertilizers to evaluate which one presents the best production and the best alternative for the producer. The poultry manure was different compared to the other fertilizers, showing a greater height and stem diameter. The organic fertilizer that stood out was the poultry manure, which showed a higher sorghum production in relation to the other treatments, confirming the positivity of its use.